2020
DOI: 10.3390/microorganisms8030417
|View full text |Cite
|
Sign up to set email alerts
|

A Review and Perspective of eDNA Application to Eutrophication and HAB Control in Freshwater and Marine Ecosystems

Abstract: Changing ecological communities in response to anthropogenic activities and climate change has become a worldwide problem. The eutrophication of waterbodies in freshwater and seawater caused by the effects of human activities and nutrient inputs could result in harmful algae blooms (HABs), decreases water quality, reductions in biodiversity and threats to human health. Rapid and accurate monitoring and assessment of aquatic ecosystems are imperative. Environmental DNA (eDNA) analysis using high-throughput sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 95 publications
0
20
0
Order By: Relevance
“…Eutrophication was not associated with water pollution until the 1930s, but the continuous occurrence of eutrophication worldwide has aroused global attention for its main cause of pollution [ 2 ]. Due to the rapid growth in the process of eutrophication and the slow recovery of eutrophic water, the management and treatment of plant growth is difficult and expensive [ 3 , 4 , 5 ]. Inland lakes are often strongly affected by environmental changes owing to the increasing impact of human activities.…”
Section: Introductionmentioning
confidence: 99%
“…Eutrophication was not associated with water pollution until the 1930s, but the continuous occurrence of eutrophication worldwide has aroused global attention for its main cause of pollution [ 2 ]. Due to the rapid growth in the process of eutrophication and the slow recovery of eutrophic water, the management and treatment of plant growth is difficult and expensive [ 3 , 4 , 5 ]. Inland lakes are often strongly affected by environmental changes owing to the increasing impact of human activities.…”
Section: Introductionmentioning
confidence: 99%
“…Allows rapid detection of harmful microorganisms and HABs, 245,246 but dependent on reference libraries, which are currently lacking (+/−)…”
Section: Potential Habitat Provisioning Of Macroalgal Cultivation For...mentioning
confidence: 99%
“…Recent studies have shown the abundant amount of RNA persisting in the environment to measure gene expression [ 40 , 41 ]. The eRNA collected on biofilm matrix shows its prolonged persistence (21 days) [ 42 ]. There is some evidence showing that eRNA is more sensitive biomarker of environmental insults and may persist for a long period of time, particularly within extracellular vesicles or protein capsids [ 43 ].…”
Section: Can Edna/erna Biomonitor the Exposome?mentioning
confidence: 99%